2019
DOI: 10.1016/j.biotechadv.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

On top of biosynthetic gene clusters: How epigenetic machinery influences secondary metabolism in fungi

Abstract: Fungi produce an abundance of bioactive secondary metabolites which can be utilized as antibiotics and pharmaceutical drugs. The genes encoding secondary metabolites are contiguously arranged in biosynthetic gene clusters (BGCs), which supports co-regulation of all genes required for any one metabolite. However, an ongoing challenge to harvest this fungal wealth is the finding that many of the BGCs are ‘silent’ in laboratory settings and lie in heterochromatic regions of the genome. Successful approaches allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
110
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 169 publications
2
110
0
3
Order By: Relevance
“…Genes that are involved in secondary metabolism are sequentially distributed in biosynthetic gene clusters (BGCs), providing the coordinated regulation of the genes that are related to any metabolite [89]. The treatment with DNA methylation inhibitors, such as 5-azacytidine (5-AC) and RG-108, which are commonly used to inhibit the activity of DNA MTases, have been successfully confirmed to induce the expression of silent BGCs and influence secondary metabolites in Alternaria species [90], A. niger [91], Cladosporium cladosporioides [92], Diatrype sp.…”
Section: Association Between Dna Methylation and Secondary Metabolismmentioning
confidence: 99%
“…Genes that are involved in secondary metabolism are sequentially distributed in biosynthetic gene clusters (BGCs), providing the coordinated regulation of the genes that are related to any metabolite [89]. The treatment with DNA methylation inhibitors, such as 5-azacytidine (5-AC) and RG-108, which are commonly used to inhibit the activity of DNA MTases, have been successfully confirmed to induce the expression of silent BGCs and influence secondary metabolites in Alternaria species [90], A. niger [91], Cladosporium cladosporioides [92], Diatrype sp.…”
Section: Association Between Dna Methylation and Secondary Metabolismmentioning
confidence: 99%
“…In recent years, epigenetic and consequent histone posttranslational modifications have been shown to play an important role in secondary metabolite production in fungi (Pfannenstiel and Keller, 2019), including regulation of several Aspergillus and Fusarium mycotoxins such as aflatoxin, fumonisin and trichothecenes (Visentin et al, 2012;Liu et al, 2015;Yang et al, 2016;Pfannenstiel et al, 2018). Most studies investigated the role of histone modifying enzymes, such as methylases or histone deacetylases in modulating secondary metabolite synthesis in fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic surveys have revealed that fungal species typically harbour 30–100 biosynthetic gene clusters (BGCs) each encoding the biosynthetic pathway required to produce a SM(s) 3 . However, the vast majority of BGCs remain uncharacterised or ‘cryptic’ as the products they encode are undetectable under standard culture conditions, often because BGCs remain ‘silent’ or lowly expressed due to tight regulatory control 1,4 . Filamentous fungi, which have yielded a plethora of SMs with pharmaceutical and agricultural applications 5 , thus serve as attractive targets for genome mining of novel molecules.…”
Section: Introductionmentioning
confidence: 99%